Assessment of heavy metal contamination in Cystoseira sp. and ecologically distinct fish species from Northern Cyprus - Akbora, Hasan Deniz; Cicek, Burak Ali; Ayas, Deniz (Pergamon-Elsevier Science Ltd, 2026)
In this study, Cystoseira sp. samples were collected by snorkeling during summer and winter from five coastal sites within the territorial waters of Northern Cyprus. In addition, herbivorous and carnivorous fish species inhabiting demersal, rocky-sandy, and epipelagic zones were obtained from local fishers across four representative regions. Concentrations of Ag, Al, As, Cd, Cr, Cu, Fe, Pb, Se, Sr, V, and Zn were measured in Cystoseira sp., and in fish liver and muscle tissues using inductively coupled plasma optical emission spectrometry (ICP-OES). Results were compared with previous studies conducted in Cyprus and neighboring Eastern Mediterranean countries. A significant negative correlation was observed between fish trophic levels and concentrations of Cu, Fe, Pb, Sr, and Zn. Metal concentrations were further evaluated against national and international food safety and environmental standards. Notably, some fish muscle samples contained As, Cd, and Pb above permissible limits, suggesting potential risks to human health. To further assess this issue, a human health risk evaluation (non-carcinogenic and carcinogenic) was performed under a realistic exposure scenario of two meals per week. All Hazard Index (HI) values were below 1, demonstrating no non-carcinogenic risk for either adults or children. Carcinogenic risk (CR) values were generally insignificant (<10(-6)), although As and Cd in some species reached the tolerable range (10(-6)-10(-4)) for children, while only As posed tolerable risk levels in adults. Furthermore, elevated As levels in marine organisms may be associated with agricultural runoff, emphasizing the need for tighter monitoring of agricultural practices in coastal areas.
Keywords: Marine pollution; Environmental risk assessment; Trace metal contamination; Trophic levels; Bioaccumulation; Health risk assessment